Linguistic expressions of negative stances: A conversation analysis of turn-medial particle dai in Jishou dialect (Hunan Province, China) - Liu, Feng; Li, Xi; Liu, Rurong; Zeng, Jianyu (Frontiers in Psychology, 2023)
The study focuses on the syntactic functions and prosodic features of the turn-media particle dai in Jishou dialect, Hunan Province, China, as well as its distributions and interactional functions across eight different contexts. The research utilizing a corpus of 70 h consisting of 300,000 characters of the Jishou dialect, employed the conversation analysis (CA) method to analyze the interactional behaviors of dai. The results show that dai serves as an overt marker of speakers' negative stances, including complaining and criticizing. It is treated as an emerging product continuously shaped by diverse factors, such as context, sequential positioning, prosodic manifestation in talk-in-interaction, and its influence on the subsequent development of the conversation.